2015
DOI: 10.1245/s10434-015-4717-7
|View full text |Cite
|
Sign up to set email alerts
|

Normal Axillary Ultrasound Excludes Heavy Nodal Disease Burden in Patients with Breast Cancer

Abstract: Patients with normal axillary physical exam and ultrasound rarely harbor a large nodal disease burden. Randomized trials of sentinel lymph node biopsy versus no axillary surgery in patients with normal AUS must be powered for subgroup analysis of patients with invasive lobular carcinoma and pT2-pT4 tumors. Preoperative identification of nodal metastasis may decrease the need for second surgeries and identify candidates for neoadjuvant chemotherapy. AUS is a noninvasive means of predicting disease burden preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
29
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 19 publications
5
29
2
Order By: Relevance
“…In previous single‐centre studies there has been speculation regarding the difference in AUS sensitivity based on tumour subtype. However, all of these studies included significantly lower numbers of patients compared with the present study. The majority of comparative studies, however, showed no difference in AUS sensitivity based on tumour subtype.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In previous single‐centre studies there has been speculation regarding the difference in AUS sensitivity based on tumour subtype. However, all of these studies included significantly lower numbers of patients compared with the present study. The majority of comparative studies, however, showed no difference in AUS sensitivity based on tumour subtype.…”
Section: Discussionmentioning
confidence: 58%
“…Hackney and co‐workers demonstrated that the most significant factor in producing discordance between preoperative AUS and definitive histological evidence of lymph node metastasis was the lobular subtype. In addition, Jackson et al . and Neal et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most studies have focused on the role of imaging studies in predicting the presence of nodal metastasis rather than evaluating the quantitative burden of nodal disease. Axillary ultrasound is an imaging modality associated with low cost and risk and is also reported to have high sensitivity in excluding or predicting heavy nodal burden [1618]. However, quantification of nodal disease using ultrasound is difficult and operator dependent, which compromises the objectivity of the imaging test.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, in the subgroup of patients with T1 tumours, a negative axillary ultrasound examination is indicative of a low axillary burden so that further axillary staging can potentially be avoided. Jackson et al ,. in a retrospective analysis of 513 patients with T1–T4 breast cancer, reported that the positive predictive value (PPV) and NPV for detecting more than two macrometastases were 31 and 86 per cent respectively, with a false‐negative rate of 4 (95 per cent c.i.…”
mentioning
confidence: 99%